# What is the solution of the system of equations? y = 3x + 7 and y = x - 9

**Solution:**

It is given that,

y = 3x + 7 and y = x - 9

**Let us assume, **

y = 3x + 7 … [equation 1]

**Also assume,**

y = x - 9 … [equation 2]

**Consider equation 1 and substitute the value of equation 2 in equation 1,**

y = 3x + 7

x - 9 = 3x + 7

**By transposing we get,**

3x - x = - 9 - 7

2x = -16

x = -16/2

x = -8

**Now, substitute the value of x in equation 2 we get,**

y = x - 9

y = - 8 - 9

y = - 17

**Therefore, the solution of the system of equations is x = - 8, y = - 17.**

## What is the solution of the system of equations? y = 3x + 7 and y = x – 9

**Summary:**

The solution of the system of equations y = 3x + 7 and y = x - 9 is x = - 8, y = - 17.